2022
DOI: 10.1007/s10995-022-03492-5
|View full text |Cite
|
Sign up to set email alerts
|

Housing Stability and Access to General Healthcare and Reproductive Healthcare Among Women in Ohio

Abstract: Background The relationship between housing instability and reproductive healthcare is understudied. We examined the association between housing insecurity and access and utilization of general healthcare, contraceptive healthcare, and abortion care. Methods Using data from a population-representative survey of adult reproductive-age Ohio women (N = 2,529), we assessed housing insecurity (not paying rent/mortgage on time in the past year). We examined associations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Still, across the study populations, at least 20% reported not getting desired health care, and between 10% (Iowa and Wisconsin aged 18-44) and 19% (Arizona family planning clinic patients) had trouble or delays in obtaining their desired method of birth control in the past year, indicating that a significant proportion of women in all study populations are not fully getting their sexual and reproductive health care needs met. These levels of not being able to access desired health care and trouble in accessing contraception among reproductive-aged women are comparable to those documented among a similar population in Ohio during the same timeframe [15]. We found that cost is a primary barrier to healthcare services broadly and desired contraception specifically.…”
Section: Plos Onesupporting
confidence: 75%
See 1 more Smart Citation
“…Still, across the study populations, at least 20% reported not getting desired health care, and between 10% (Iowa and Wisconsin aged 18-44) and 19% (Arizona family planning clinic patients) had trouble or delays in obtaining their desired method of birth control in the past year, indicating that a significant proportion of women in all study populations are not fully getting their sexual and reproductive health care needs met. These levels of not being able to access desired health care and trouble in accessing contraception among reproductive-aged women are comparable to those documented among a similar population in Ohio during the same timeframe [15]. We found that cost is a primary barrier to healthcare services broadly and desired contraception specifically.…”
Section: Plos Onesupporting
confidence: 75%
“…Presenting both domains allows for a richer description of the overall healthcare access context in which people are seeking SRH care. For example, a 2018–2019 survey among Ohio women revealed that more than a quarter of this group was unable to access general healthcare whereas about 10% had experienced delays or difficulties in accessing contraceptive care, suggesting that the ability to obtain contraceptive care is not an indicator of general healthcare access, and vice versa [ 15 ].…”
Section: Introductionmentioning
confidence: 99%